2017
DOI: 10.1371/journal.pone.0170674
|View full text |Cite|
|
Sign up to set email alerts
|

Fluoride Regulate Osteoblastic Transforming Growth Factor-β1 Signaling by Mediating Recycling of the Type I Receptor ALK5

Abstract: This study aimed to preliminary investigate the role of activin receptor-like kinase (ALK) 5 as one of TGF-βR1 subtypes in bone turnover and osteoblastic differentiation induced by fluoride. We analyzed bone mineral density and the expression of genes related with transforming growth factor-β1(TGF-β1) signaling and bone turnover in rats treated by different concentrations of fluoride with or without SB431542 in vivo. Moreover, MTT assay, alkaline phosphatase staining, RT-PCR, immunocytochemical analysis and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“… 56 Moreover, the TGF-I ameliorated the abnormal role of high levels of active TGF-β1 in bone formation and directly attenuated Smad2/3 phosphorylation. 57 , 58 In our study, injection of the TGF-I significantly decreased the number of p-Smad2/3-positive cells in the condylar cartilage and subchondral bone in the TMD model. The significant increase in Osterix-positive cells in the subchondral bone of the TGF-I group may trigger the bone formation process and lead to increased bone mass in subchondral bone.…”
Section: Discussionsupporting
confidence: 58%
“… 56 Moreover, the TGF-I ameliorated the abnormal role of high levels of active TGF-β1 in bone formation and directly attenuated Smad2/3 phosphorylation. 57 , 58 In our study, injection of the TGF-I significantly decreased the number of p-Smad2/3-positive cells in the condylar cartilage and subchondral bone in the TMD model. The significant increase in Osterix-positive cells in the subchondral bone of the TGF-I group may trigger the bone formation process and lead to increased bone mass in subchondral bone.…”
Section: Discussionsupporting
confidence: 58%
“…The mineralization state, formation of inorganic calcium is studied using alizarin red staining wherein the inorganic calcium deposition acts as a marker of mineralization and osteogenesis 23,24 . hDFSCs cultured in NCM in the presence of higher concentration of both silicate platelets (NS − F or NS + F) such as 50 µg.mL −1 and 100 µg.mL −1 , show mineral deposition (calcium staining by alizarin red).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these NS may provide sites for mineralization. It is reported that fluoride down-regulates TGF-β1 signaling 37 , and also up regulates bone mineralization by enhancing osteoblast differentiation 24 , and stimulating alkaline phosphatase (ALP) activity and OPN, a matrix protein found in mineralized tissues and plays a pivotal role in modulating osteoclastic activities. These in vitro studies have demonstrated that NS have an anabolic effect on enhancement of hDFSCs differentiation to osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Another putative causal SNP, rs4776341, overlaps with an active enhancer-type chromatin in osteoblasts, is an intronic variant located in the sterile alpha motif domain containing 3 (SMAD3) gene, which is part of the important TGF-β1 signaling pathway for osteoblast and osteoclast differentiation via the TGF-β1 signaling pathway ( Yang et al, 2017 ). Interestingly, the SNP rs4776341 is associated with eBMD and FNK-BMD by the cFDR method.…”
Section: Discussionmentioning
confidence: 99%